Coal Workers' Pneumoconiosis at PT. A Sawahlunto and The Influencing Factors - Ulfahimayati Ulfahimayati; Deddy Herman; Masrul Basyar; Fenty Anggrainyi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Coal workers’s pneumoconiosis (black lung disease) is an interstitial lung disease caused by chronic inhalation of coal dust. The incidence of coal workers’s pneumoconiosis increased globally from the 1990s to the 2000s by 3.2%. Indonesia is the country which has many coal mining, but national prevalence of coal workers pneumoconiosis was not discovered. PT. A is one of mining companies in Sawahlunto. The aims of this study was to determine the incidence of coal workers’ pneumoconiosis at PT. A Sawahlunto and it’s influencing factors. Methods: This study is an analytic study with cross sectional design, conducted from November 2019 to April 2020. There were 90 coal miners participated in this study. All subjects were performed chest X-ray examination with ILO standard to asses the incidence of pneumoconiosis. Spirometr examination, dust level measurement with portable low volume air sampler, interview, and validated questionnare were performed to evaluate it’s influencing factors. Statistical analysis used Chi-square test and double logistic regression test. Results: This study found 12 workers (13.3%) had pneumoconiosis. From the statistical test results obtained age >50 years (P=0.035), duration of exposure (P=0.040), mask usage (P=0.029), restrictive lung function (P=0.004), and the mixed abnormality lung function (P=0.006) is associated with pneumoconiosis. The most dominant factor was mask usage (P=0.049) with OR=5.026 Conclusion: The most dominant factor that influence coal workers’ pneumoconiosis was mask usage. Others related factors were age, duration of exposure and abnormality lung function.